2018
DOI: 10.1093/ofid/ofy040
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Packages to Reduce the Impact of HIV and HCV Infections Among People Who Inject Drugs in Eastern Europe and Central Asia: A Modeling and Cost-effectiveness Study

Abstract: BackgroundWe evaluated the effectiveness and cost-effectiveness of interventions targeting hepatitis C virus (HCV) and HIV infections among people who inject drugs (PWID) in Eastern Europe/Central Asia. We specifically considered the needle-syringe program (NSP), opioid substitution therapy (OST), HCV and HIV diagnosis, antiretroviral therapy (ART), and/or new HCV treatment (direct acting antiviral [DAA]) in Belarus, Georgia, Kazakhstan, Republic of Moldova, and Tajikistan.MethodsWe developed a deterministic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 15 publications
(19 reference statements)
2
27
0
Order By: Relevance
“…Whilst the right to health suggests that anyone infected with HCV should have access to treatment, irrespective of disease stage and drug use , some people must pay for them out of pocket in those countries where high costs and/or discrimination have led to reimbursement restrictions. Most countries that subsidize DAA therapy have restricted access in terms of who can prescribe and disease severity , despite evidence that treatment is cost‐effective when the long‐term costs of morbidity, mortality and onward transmission are included in the calculations, and provided that harm reduction is widely available . Strategies that have proven successful in bringing DAA costs down to a fraction of the list price include directly negotiating with pharmaceutical companies, licensing generics and committing to scaling up treatment in order to secure bulk discounts and achieve economies of scale .…”
Section: The Model Of Care (Moc): a Tool For Increasing Treatment Covmentioning
confidence: 99%
“…Whilst the right to health suggests that anyone infected with HCV should have access to treatment, irrespective of disease stage and drug use , some people must pay for them out of pocket in those countries where high costs and/or discrimination have led to reimbursement restrictions. Most countries that subsidize DAA therapy have restricted access in terms of who can prescribe and disease severity , despite evidence that treatment is cost‐effective when the long‐term costs of morbidity, mortality and onward transmission are included in the calculations, and provided that harm reduction is widely available . Strategies that have proven successful in bringing DAA costs down to a fraction of the list price include directly negotiating with pharmaceutical companies, licensing generics and committing to scaling up treatment in order to secure bulk discounts and achieve economies of scale .…”
Section: The Model Of Care (Moc): a Tool For Increasing Treatment Covmentioning
confidence: 99%
“…Seventeen studies assessed the costs and effects of screening programs and antiviral treatments: seven evaluated screening in general population or subgroup of general population, five in people who inject drugs, four in high‐risk populations and three in other populations . It is to be noted here that two studies evaluated the cost‐effectiveness of HCV screening in more than one population group (general and high‐risk population, and people who inject drugs and high‐risk population).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies included in this group were cost‐utility analysis and estimated the ICER as € per QALY gained, and one study was a cost‐effectiveness analysis with the ICER reported as € per life year saved (Table S3). One study was multi‐country and assessed the screening programs in five Eastern Europe countries . In all these studies, the simulated population was people who inject drugs currently or previously in charge to addition care centres (Table S3 and Data S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations